OPTIMIZATION SCHEDULING PROJECT REHABILITATION BUILDING AND HALL DEKRANASDA AND KALIMANTAN BARAT MUSEUM FENCE USING CRITICAL PATH METHOD (CPM) - Halim, Layla Mutiara; Lusiana, Lusiana; Nuh, Safarudin M. (Fakultas Teknik Universitas Tanjungpura, 2024)
This study investigates the optimization of project scheduling using the Critical Path Method (CPM) in construction projects. Focusing on the Building Rehabilitation Project, Dekranasda Hall, and Kalimantan Barat Museum Fence, the research aims to reduce project duration without altering costs. CPM is employed to map out activities in a network, identifying the critical path to enhance time management. The initial project duration was 249 days. By breaking down work items and increasing the number of workers in critical activities, the duration was reduced to 125 days. Optimization involved dividing tasks into manageable segments and determining the appropriate workforce through trial and error. The study demonstrates that effective project scheduling and resource allocation can significantly reduce completion time, highlighting CPM's value in project management for achieving efficiency and meeting deadlines. The findings emphasize the importance of detailed planning, dependency logic, and continuous monitoring to optimize construction project timelines.